Identification of the fault location for three-terminal transmission lines using discrete wavelet transforms - Chiradeja, P.; Pothisarn, C. (My University, 2009)
This paper proposes a technique to detect fault locations in a three-bus transmission system using discrete wavelet transform (DWT). The comparison among the first peak time in first scale of each terminal (buses) that can detect fault is performed and the two fastest first peak time obtained from comparison are used as an input data for traveling wave equation later. A comparison of results obtained from three different types of mother wavelet is discussed in order to identify the fault locations with an application of traveling wave theory. It is shown that the db4 mother wavelet produces better results than those from 'sym4' and 'coif4', with a mean error of less than 400 m.
Keywords: ATP/EMTP; Discrete wavelet transform; Fault location; Transmission line